Reconstructing the genetic structure of the Kazakh from clan distribution data - M. K. Zhabagin; О. Е. Balanovsky; Zh. M. Sabitov; A. Z. Temirgaliyev; A. T. Agdzhoyan; S. M. Koshel; Е. М. Ramankulov; E. V. Balanovska (Вавиловский журнал генетики и селекции)
Applying quasigenetic markers - non-biological traits which are nevertheless inherited in generations - is one of the research fields within human population genetics. For the West European, East European, and Caucasus populations, surnames are typical quasigenetic markers. For Central Asian populations, particularly Kazakh, the clan affiliation serves as a good marker: a set of papers demonstrated that many clans include mainly persons which biologically descent from a recent common ancestor. In this study, we analyzed a large (~4.2 million persons) dataset on quasigenetic markers - the geographic distribution of 50 Kazakh clans at the beginning of the 20th century, and compared the dataset with the direct data of the Y-chro-mosomal diversity in modern Kazakh populations. The analysis included three steps: the isonymy method, which is standard for quasigenetic markers, comparing frequencies of quasigenetic markers, and comparing the quasigenetic and genetic datasets. We constructed 50 maps of frequency of the distribution of each clan and revealed that these maps correlate with the maps of genetic distances. The Mantel test also demonstrated a significant correlation between geographic and quasigenetic distances (г = 0.60; p < 0.05). The analysis of inter-population variability revealed the largest diversity between geographic territories corresponding to the social-territorial groups of the Kazakh Khanate (zhuzes) rather than to other historical groups that existed on the territory of Kazakhstan in preceding and modern epochs. The same is evidenced by the principal components and multidimensional scaling plots, which grouped geographic populations into three clusters corresponding to three zhuzes. This indicates that the final structuring of the Kazakh gene pool might have occurred during the Kazakh Khanate period.